Soil-transmitted helminth infections and nutritional status in school-age children from rural communities in Honduras. - Ana Lourdes Sanchez; Jose Antonio Gabrie; Mary-Theresa Usuanlele; Maria Mercedes Rueda; Maritza Canales; Theresa W Gyorkos (Public Library of Science (PLoS), 2013)
Soil-transmitted helminth (STH) infections are endemic in Honduras and efforts are underway to decrease their transmission. However, current evidence is lacking in regards to their prevalence, intensity and their impact on children's health.To evaluate the prevalence and intensity of STH infections and their association with nutritional status in a sample of Honduran children.A cross-sectional study was done among school-age children residing in rural communities in Honduras, in 2011. Demographic data was obtained, hemoglobin and protein concentrations were determined in blood samples and STH infections investigated in single-stool samples by Kato-Katz. Anthropometric measurements were taken to calculate height-for-age (HAZ), BMI-for-age (BAZ) and weight-for-age (WAZ) to determine stunting, thinness and underweight, respectively.Among 320 children studied (48% girls, aged 7-14 years, mean 9.76 ± 1.4) an overall STH prevalence of 72.5% was found. Children >10 years of age were generally more infected than 7-10 year-olds (p = 0.015). Prevalence was 30%, 67% and 16% for Ascaris, Trichuris and hookworms, respectively. Moderate-to-heavy infections as well as polyparasitism were common among the infected children (36% and 44%, respectively). Polyparasitism was four times more likely to occur in children attending schools with absent or annual deworming schedules than in pupils attending schools deworming twice a year (p<0.001). Stunting was observed in 5.6% of children and it was associated with increasing age. Also, 2.2% of studied children were thin, 1.3% underweight and 2.2% had anemia. Moderate-to-heavy infections and polyparasitism were significantly associated with decreased values in WAZ and marginally associated with decreased values in HAZ.STH infections remain a public health concern in Honduras and despite current efforts were highly prevalent in the studied community. The role of multiparasite STH infections in undermining children's nutritional status warrants more research.